2015 IEEE 13th International Conference on Industrial Informatics (INDIN) 2015
DOI: 10.1109/indin.2015.7281852
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an extended prediction self-adaptive controller using LabVIEW<sup>TM</sup>

Abstract: -The implementation of the Extended Prediction SelfAdaptive Controller is presented in this paper. It employs LabVIEW TM graphical programming of industrial equipment and it is suitable for controlling fast processes. Three different systems are used for implementing the control algorithm. The research regarding the controller design using graphical programming demonstrates that a single advanced control application can run on Windows, real time operating systems and FPGA targets without requiring significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The comparison between the three systems has shown that this type of complex algorithms can operate on cheaper FPGA chips, such as the Spartan-6 and Zynq, achieving not only the same levels of computational performance as their more complex and more expensive counterparts but also important power savings. This comparison regarding the implementation on various FPGA targets and microcontrollers represents one of the main contributions and original elements in comparison to previous research [10], also including comparative tables and benchmarks for resource allocation in FPGAs. This paper also presents the diagrams implemented using LabVIEW.…”
Section: A Portable Implementation On Industrial Devices Of a Predictmentioning
confidence: 99%
“…The comparison between the three systems has shown that this type of complex algorithms can operate on cheaper FPGA chips, such as the Spartan-6 and Zynq, achieving not only the same levels of computational performance as their more complex and more expensive counterparts but also important power savings. This comparison regarding the implementation on various FPGA targets and microcontrollers represents one of the main contributions and original elements in comparison to previous research [10], also including comparative tables and benchmarks for resource allocation in FPGAs. This paper also presents the diagrams implemented using LabVIEW.…”
Section: A Portable Implementation On Industrial Devices Of a Predictmentioning
confidence: 99%